2014
DOI: 10.1080/14765284.2013.875287
|View full text |Cite
|
Sign up to set email alerts
|

The West’s aid dilemma and the Chinese solution?

Abstract: There are currently two contrasting approaches towards aid policy in Africa: that followed by the West is well known for its conditionality and selectivity and focus on direct financial support, while the approach adopted by China eschews conditionality and concentrates on infrastructure building. The Chinese approach has been criticized for its failure to create direct employment and because, it is argued, its unconditionality hampers good governance in Africa. However, this paper argues that the West faces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…China's growing foreign aid program poses a series of challenges to the existing nexus established by the OECD-DAC and the World Bank Dreher et al, 2011). There has been extensive discussion on whether Chinese foreign aid, which allegedly does not impose political conditions on recipient countries, is a better alternative to western foreign aid in terms of fostering local capacity and good governance (Sorensen, 2010;Wang et al, 2014). Debate has centered on whether aid from China and other emerging donors has bolstered rogue states, fuelled corruption and increased the debt of poor countries (Woods, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…China's growing foreign aid program poses a series of challenges to the existing nexus established by the OECD-DAC and the World Bank Dreher et al, 2011). There has been extensive discussion on whether Chinese foreign aid, which allegedly does not impose political conditions on recipient countries, is a better alternative to western foreign aid in terms of fostering local capacity and good governance (Sorensen, 2010;Wang et al, 2014). Debate has centered on whether aid from China and other emerging donors has bolstered rogue states, fuelled corruption and increased the debt of poor countries (Woods, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…China's BRI aims to assist developing countries providing an opportunity for development, respect for their rights to develop, by providing development funds, by unconditional aid, and by building infrastructure in these countries. (Wang, Ozanne, and Hao 2014;Lin and Wang 2017b). The best form of globalization is one where every country and every firm has a place in the economic ecosystem, and each country contributes to the international division of labour according to their comparative advantage, and thereby gets to enjoy the consumer products and reach a higher level of prosperity.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that China's aid has a positive impact on the recipient countries' international trade, retail, and manufacturing industries [29][30][31]. The construction of infrastructure in China's foreign aid projects has substantially boosted the economic growth of recipient countries [3,4,8,9,32]. China's assistance can also effectively mitigate the conflict caused by the abrupt withdrawal of western assistance [33,34].…”
Section: Literature Review and Theoretical Framework 21 Literature Re...mentioning
confidence: 99%